Pengaruh Harga dan Tempat terhadap Kepuasan Wisatawan dengan Loyalitas Wisatawan sebagai Variabel Intervening Pada Wisata Rekreasi Air Buatan (Waterpark) Kota Palembang - Benklah, Jihan Qatrunnada; Rahayu, Sri; AM, Trisniarty (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to determine the effect of prices and places on tourist satisfaction with employee loyalty variables as intervening variables in artificial water recreational tourism (waterpark) Palembang City. The research method used is associative research using primary data. The population in this study is tourists who have visited the Artificial Water Recreation Tour (Waterpark) of Palembang City, while the population nature is infinite. Samples were taken using the minimum sample size of 5 to 10 observations for each estimated parameter/indicator so that the total sample was 12 indicators x 10 reaching 120 respondents. Sampling technique with probability sampling with cluster random sampling method. This researcher uses the SEM method with the help of SmartPLS software. The results of this study show that: 1) There is a positive and significant influence of prices on tourist satisfaction on Artificial Water Recreation Tourism (Waterpark) Palembang City 2) There is a positive and significant influence of the place on tourist satisfaction on Artificial Water Recreation Tourism (Waterpark) Palembang City. 3) There is a positive and insignificant influence on the price on tourist loyalty to the Palembang City Artificial Water Recreation Tour (Waterpark). 4) There is a positive and insignificant influence of the place on tourist loyalty to the Artificial Water Recreation Tour (Waterpark) palembang city. 5) There is a positive and significant influence of price on tourist satisfaction and an impact on tourist loyalty to the Artificial Water Recreation Tour (Waterpark) palembang city. 6) There is a positive and significant influence of the place on tourist satisfaction and an impact on tourist loyalty to the Artificial Water Recreation Tour (Waterpark) of Palembang City. 7) There is a positive and significant influence of tourist satisfaction on tourist loyalty to the Artificial Water Recreation Tour (Waterpark) palembang city